2014
DOI: 10.1080/10934529.2014.928497
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in brown bears (Ursus arctos) from Croatia: Relation to cadmium and mercury

Abstract: Muscle (n = 111), liver (n = 111), and kidney cortex (n = 101) samples from brown bears (Ursus arctos) were collected in the 2009 and 2010 hunting seasons in Croatia and analysed for selenium (Se), cadmium (Cd), and total mercury (Hg). The aim was to assess the levels of these elements according to age, sex, and season of collection, and to investigate possible Se/Cd and Se/Hg interactions. Median Se concentrations were 0.139 μg/g in muscle, 0.409 μg/g in liver and 1.75 μg/g wet mass in kidney cortex. Median C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Molar ratios of unity or lower imply that the available Se levels are not enough to detoxify Hg presently, binding it to an inert complex that precipitates [ 91 ]. The median liver Se/Hg molar ratio in our bears was similar to the ratios reported previously for Croatian bears (26 vs. 34, respectively [ 47 ]), but five times lower than in the livers of Croatian wolves. Such results reflect lower Hg levels in wolf livers and higher Se levels compared to bears, meaning that wolves are at lower risk of Hg-related toxicity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Molar ratios of unity or lower imply that the available Se levels are not enough to detoxify Hg presently, binding it to an inert complex that precipitates [ 91 ]. The median liver Se/Hg molar ratio in our bears was similar to the ratios reported previously for Croatian bears (26 vs. 34, respectively [ 47 ]), but five times lower than in the livers of Croatian wolves. Such results reflect lower Hg levels in wolf livers and higher Se levels compared to bears, meaning that wolves are at lower risk of Hg-related toxicity.…”
Section: Discussionsupporting
confidence: 90%
“…The most studied interaction of Hg with an essential element is that with Se and Se-containing compounds resulting in Hg sequestration, especially in the liver, but also in the kidney and brain [ 11 , 34 ]. Previous wildlife studies reported concurrent accumulations of Hg and Se in the liver and kidney [ 47 , 87 , 88 , 89 , 90 ], but brain samples did not follow this trend due to the limited Hg levels which were greatly surpassed by Se levels in polar bears [ 29 ], as well as in our brown bears and wolves. The Se/Hg molar ratios in Croatian bear and wolf brains were similar (128 and 161, respectively) and more than 20 times higher than in polar bears’ brain stems (5.6 [ 29 ]).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, the vast majority of game is not controlled for residues because non-marketed food is not subject to these tests. Data about toxic metal levels in free-living game from Croatia are mainly limited to scientific research (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). In 2012, the Croatian Food Agency published a heavy metal exposure assessment (40) based on data for wild boar meat, liver, and kidney.…”
mentioning
confidence: 99%